The Influence of Sekolah Penggerak and Teacher Performance on the Quality of Elementary School Graduates - Abdurahman, Ayi; Setiawati; Hidayat, Ujang Syarif; Budiman, Dana; Pradesa, Kohar (Universitas Pendidikan Ganesha, 2023)
Sekolah penggerak aims to improve the quality of learning in schools and encourage the adoption of innovations in education. The program of Sekolah penggerak needs the performance of teachers who have important tasks and determine the quality of learning and the quality of graduates. Teacher performance will likely have an impact on the performance of educational institutions and can produce quality graduates. In this study, the variables that are the focus of research as regressors are Sekolah penggerak and Teacher Performance. This study aims to analyze the effect of Sekolah Penggerak and Teacher Performance on the Quality of Graduates in Elementary Schools. The research method used was a questionnaire given to teachers as a population with several statements provided. Data were analyzed statistically using descriptive methods, simple linear regression, and multiple linear regression. The results show that Sekolah penggerak and Teacher Performance significantly affect the Quality of Graduates variable.